The psychological and physiological consequences of low energy availability in a male combat sport athlete - Langan-Evans, C.; Germaine, M.; Artukovic, M.; Oxborough, D. L.; Areta, J. L.; Close, G. L.; Morton, J. P. (Medicine & Science in Sports & Exercise, 2021)
Purpose: This study aimed to evaluate the effects of low energy availability (EA) on health and performance indices associated with the Male Athlete Triad and Relative Energy Deficiency in Sport (RED-S) models. Methods: Over an 8-wk period, a male combat sport athlete adhered to a phased body mass (BM) loss plan consisting of 7-wk energy intake (EI) equating to resting metabolic rate (RMR) (1700 kcal·d-1) (phase 1), 5 d of reduced EI (1200-300 kcal·d-1) before weigh-in (phase 2), and 1 wk of ad libitum EI postcompetition (phase 3). EA fluctuated day by day because of variations in exercise energy expenditure. Regular assessments of body composition, RMR, cardiac function, cardiorespiratory capacity, strength and power, psychological state and blood clinical chemistry for endocrine, bone turnover, hydration, electrolyte, renal, liver, and lipid profiles were performed. Results: BM was reduced over the 8-wk period by 13.5% (72.5 to 62.7 kg). No consequences of Male Athlete Triad or RED-S were evident during phase 1, where mean daily EA equated to 20 kcal·kg·fat free mass (FFM)-1·d-1 (range, 7 to 31 kcal·kg/FFM·d) and BM and fat mass (FM) losses were 6.5 and 4.4 kg, respectively. However, consequences did present in phase 2 when mean daily EA was consistently <10 kcal·kg/FFM·d, as evidenced by alterations to endocrine hormones (e.g., testosterone <5 nmol/L) and reduced RMR (-257 kcal/d). Conclusion: Data demonstrate that 7 wk of daily fluctuations in EA equating to a mean value of 20 kcal·kg FFM/d permits reductions of BM and FM without perturbations to physiological systems associated with the Male Athlete Triad and RED-S. By contrast, a subsequent period of five consecutive days of EA <10 kcal·kg FFM·d induced consequences of Male Athlete Triad and RED-S.